UNJUSTIFIED ENRICHMENT: HAVING A FRIEND WEARING DIFFERENT HATS, WHO NEEDS ENEMIES? Mndi v Malgas 2006 2 SA 182 (EPD) - PJ Badenhorst; Lindi Coetzee (Obiter, 2022)
The decision in the present case is important for enrichment law within the context of the confirmation and application of : (a) the general requirements of an enrichment action; and (b) the quantum rule pertaining to an enrichment claim. The identification of the particular enrichment action and the specific requirements thereof did not receive the express attention of the court. It will be shown that the approach of the court of relying only on the general requirements of an enrichment action can only be followed if thespecific requirements of the appropriate condictio would not have led to a different result. Application of one of the requirements of the condictio indebiti, namely that the undue payment must legally be considered to have been paid to the receiver (recipiens) of the payment, would have ensured a more just result by the Court. As will be seen in 5 2 below the relevance of the defence of reduction or loss of enrichment in this case has been raised by other academics and will only briefly be referred to as it falls beyond the scope of our case discussion. The decision also dealt with the issue whether the relationship between the enriched person and the other members of the club constituted a separate legal entity. The Court did not consider whether the relationship between the members of the club could have constituted a partnership and that the impoverished person contracted with the enriched person in her capacity as a partner in a partnership.